Are Amazonian fish more sensitive to ammonia? Toxicity of ammonia to eleven native species - Souza-Bastos, Luciana Rodrigues; Val, Adalberto Luis; Wood, Chris M. (Hydrobiologia, 2017)
Little is known about the tolerance of Amazonian fish to ammonia. However, elevated ammonia of anthropogenic origin may now occur. As Amazonian fish evolved in waters which are generally acidic (i.e., low NH3), we hypothesized that they would be more sensitive to ammonia than other freshwater fish. The acute (96-h) toxicity of NH4Cl was tested in native ion-poor soft water (pH 7.0, ~28 °C) using semi-static tests with 11 species. Species sensitivity distributions (SSDs) for LC5096 h and LC1096 h and calculations of the hazardous concentrations to the most sensitive 5% (HC5 values) were tabulated. Values of LC5096 h/LC1096 h (in mM total ammonia) ranged from 2.24/0.78 for Paracheirodon axelrodi (most sensitive) to 19.53/16.07 for Corydoras schwartzi (most tolerant). These results confirm our hypothesis that Amazonian fish are more sensitive to ammonia than other freshwater species. High levels of ammonia may be associated with hypoxia, especially during dry periods. Simultaneous hypoxia (15–20% saturation) exacerbated ammonia toxicity in the most sensitive species (P. axelrodi), but not in Astronotus ocellatus or Corydoras schwartzi, a facultative air-breather where prevention of air access doubled ammonia toxicity. The present data are useful in generating regulatory guidelines in Amazonian waters and indicate that further studies incorporating hypoxia and air access/denial are needed. © 2015, Springer International Publishing Switzerland.
Keywords: Air-breathing Organism; Ammonia; Anthropogenic Effect; Concentration (composition); Ecological Impact; Eco-toxicology; Finfish; Hypoxia; Native Species; Pollution Tolerance; Risk Assessment; Sublethal Effect; Toxicity Test; Amazonia; Astronotus Ocellatus; Corydoras Schwartzi; Paracheirodon Axelrodi